Spectrum of diseases and pattern of referral at the Oral Diagnosis Clinic of a tertiary dental center (Nigerian Dental Journal, 2011)
Objective: The purpose of this study was to determine the scope of oral diseases and referrals within the Dental Centre at the University of Port Harcourt Teaching Hospital (UPTH).Method: The clinic logbook of the Oral diagnosis clinic of the Dental centre, University of Port Harcourt Teaching Hospital was reviewed retrospectively over an 18-month period. Demographic and clinical data of all patients were retrieved and statistically analyzed using SPSS Version 17.0.Result: There were 2,249 patients comprising 945 (42%) males and 1,304 (58%) females. The age range was 1month to 95 years and mean age, 29.9 + 16.8 years. The mean age for male was 30.4 + 17.3years and for female, 29.5±16.4 years. Based on their age, patients were categorized into children, youth, middle age and elderly. Patronage was predominantly by the youth category (age 17- 40 years). The predominant pathology presented was complicated dental caries (41.1%). Traumatic injuries showed predilections for the male gender (87 males compared to 58 females). Most of the referrals were to the Oral and Maxillofacial Surgery Clinic (825 patients) and tooth extraction (741 adults, 147 paediatric extractions) was the major reason for referral.Conclusion: In spite of the worldwide epidemiological report of its reducing incidence, dental caries and its sequelae are still the major reasons for patronage of dental health services in our environment and dental extraction is the mostly consumed treatment modality.
Keywords: Oro-facid diseases; Dental clinic attendance; Referrals